Organophosphate induced delayed pure motor neuropathy. Issue 5 (8th May 2017) - Shukla, Abhiranjan; Anand, Dharampal; Urkude, Ravindra
Abstract : Introduction: Organophosphate poisoning (OP) is known to cause various neurological syndrome which include acute toxic effects due to cholinergic crisis and delay-ed syndrome characterised by motor-sensory polyneuropathy. Pure motor neuropathy with intact sensory conduction is rarely documented. We describe a patient who had a classic acute cholinergic crisis after exposure to organophosphate, with subsequent development of delayed pure motor axonal neuropathy. Case: A 49 years old man was admitted to ICU with cholinergic crisis due to intentional ingestion of weedkiller (endosulphan and methamidophos). At the time of admission his GCS was 3, with pin point pupils, excessive salivation, hypotension and lacrimation. He was put on mechanical ventilator and treated with atropine. He recovered from acute cholinergic crisis but after two weeks, he developed weakness in legs and bilateral foot drop. Neurological examination showed wasting of the muscles of both legs with muscle power of grade 3/5 proximally and 0/5 distally. There was no weakness of the upper limbs. DTR were absent in the lower limbs. There was no sensory deficit. Nerve conduction studies (NCS) confirmed the diagnosis of severe axonal pure motor neuropathy with normal sensory response. He noticed improvement in strength in the legs over time but follow-up NCS after two years still shows axonal motor neuropathy. Conclusions: Organophosphate-induced delayed polyneuropathy (OPIDP) is a rare toxicity resulting from exposure to certain organophosphorus (OP) esters. It is characterised by distal degeneration of some axons of both the peripheral and central nervous systems occurring 1–4 weeks after single or short-term exposures. It is presumed to be due to phosphorylation and ageing of an enzyme in axons called neurotoxic esterase or neuropathic target esterase (NTE). Chronic neurotoxicity due to organophosphorus poisoning is dependent on several factors: chemical composition and dose of the organophosphates and the administration of anticholinergic for the cholinergic crisis.